2021
DOI: 10.1016/j.carbon.2020.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio insights into the interaction mechanisms between boron, nitrogen and oxygen doped diamond surfaces and water molecules

Abstract: Diamond and diamond-like carbon coatings are used in many applications ranging from biomedicine to tribology. A wide range of dopants have been tested to modify the hydrophilicity of these surfaces, since this is central to their biocompatibility and tribological performance in aqueous environments. Despite the large number of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 78 publications
2
14
0
Order By: Relevance
“…Meanwhile, the values obtained for H2O molecules span from 0.23 eV to 0.67 eV. Our data is in good agreement with previous calculations [36,[39][40][41]. In both cases, the adsorbate tends to lay on top of the surface trenches with an equilibrium distance from the nearest carbon atom of the diamond surfaces greater than 2.28 Å.…”
Section: H2 H2o and O2 Adsorption On Diamond Surfacessupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, the values obtained for H2O molecules span from 0.23 eV to 0.67 eV. Our data is in good agreement with previous calculations [36,[39][40][41]. In both cases, the adsorbate tends to lay on top of the surface trenches with an equilibrium distance from the nearest carbon atom of the diamond surfaces greater than 2.28 Å.…”
Section: H2 H2o and O2 Adsorption On Diamond Surfacessupporting
confidence: 91%
“…The chosen thicknesses for the diamond surface models used in this study are based on a number of previous studies [39,52,53,[55][56][57], which indicates the thickness of the slabs is sufficient to produce accurate structural and energetic properties. A vacuum region of 20 Å thickness is included in the supercell to separate each slab from its periodic replicas along the [001] direction.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the hardest solid-lubricant materials, diamond or DLC films has been attracting enormous attention in the field of anti-wear design ( Kumar et al, 2011 ; Kumar et al, 2013 ; Erdemir and Martin, 2018 ; Tyagi et al, 2019 ). However, the wear resistance of diamond and DLC films is dependent on humidity and gaseous environment ( Manimunda et al, 2017 ; Huo et al, 2018 ; Wu et al, 2018 ; Yunhai Liu et al, 2019 ; Jingjing Wang et al, 2019 ; Yu et al, 2020 ; Latorre et al, 2021 ; Wang and Komvopoulos, 2021 ). Notably, the improved wear properties of diamond and DLC films are closely related to the surface passivation or shear-induced graphitization ( Bouchet et al, 2015 ; Rani et al, 2018a ; Rani et al, 2018b ).…”
Section: Diamond and Dlc Filmsmentioning
confidence: 99%
“…Conventional classical molecular dynamics (MD) simulations have been successfully applied in simulating the mechanical process in CMP, while they failed in describing the chemical reactions involved in the CMP processes. On the other hand, ab initio MD simulations provided useful insights into the tribological processes at the solid–solid and solid–liquid interfaces, but the application is limited only to investigate small systems in a very short time . Indeed, a few ab initio MD simulations studied the ceria silica interactions using small ceria clusters (H 4 Ce 6 O 12 ) interacting with model α-quartz surfaces for a few picoseconds. These theoretical studies demonstrated that the direct interaction of the ceria cluster with the dry silica surface first promoted the dissociation of the Si–O Si and Ce–O Ce bonds, and subsequently, a Si–O–Ce bond was formed.…”
Section: Introductionmentioning
confidence: 99%